Analysing the Usage Data of Open Access Scholarly Books: What Can Data Tell Us? - Ozaygen, Alkim (Curtin University, 2019)
This study explores data captured on the Internet related to OA scholarly books to provide a detailed overall picture of the dissemination of these books beginning from the point they were made OA. To uncover the factors that impact on the digital uses of OA books, it explores relationships between book characteristics and the characteristics and motivations of the groups using and sharing books in digital landscapes.